Formation and stability investigation of meso-hydroxy diacyl-dipyrromethane - Ferryansyah, Mohammad Akbar; Santria, Anas; Ishikawa, Naoto; Firmansyah, Dikhi (Communications in Science and Technology, 2025)
The oxidation of dipyrromethane by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) generally produces dipyrrin, but in the presence of trace water, a meso-hydroxy dipyrromethane can be formed. To investigate this unusual product, we then studied meso-hydroxy bis(p-anisoyl)-p-fluorophenyl dipyrromethane (3) obtained from the oxidation of bis(p-anisoyl)-p-fluorophenyl dipyrromethane (2). Spectroscopic studies (1H-NMR, UV-Vis, and fluorescence), mass spectrometry, and computational analyses were performed to investigate this mechanism. Zinc complexation of compound 3 altered the 1H-NMR spectrum and shifted the absorption peak from 325 nm to 567 nm with “turn-on” fluorescence. Thermochemical studies have indicated that the formation of meso-hydroxy requires energy higher than dipyrrin. This study suggests that the electronic properties of meso-aryl and acyl groups are the key factors for the nucleophilic attack of water on cationic dipyrromethane intermediate. These results further improve the understanding of dipyrromethane oxidation pathways, which is crucial for the design and synthesis of dipyrrin-chemosensors.